Physical insights into protection effect of conjugated polymers by natural antioxidants. Issue 3 (5th January 2021) - Xie, Mingcai; Hua, Yan; Hong, Daocheng; Wan, Sushu; Tian, Yuxi
Abstract : Single-molecule spectroscopy reveals photostability and fluorescence intensity enhancement of P3HT with addition of VE. VE as natural antioxidants play roles of a molecular triplet quencher, singlet oxygen scavenger and photooxidized defect healer. Abstract : Conjugated polymers (CPs) known as organic semiconductors have been broadly applied in photovoltaic and light emitting devices due to their easy fabrication and flexibility. However, one of the bottlenecks limiting the application of CPs is their poor photostability upon continuous excitation which is one of the crucial parameters of CPs. How to improve the photostability of CPs is always one of the key questions in this field. In this work, we found that the photostability of poly(3-hexylthiophene-2, 5-diyl) (P3HT) molecules can be largely improved by addition of vitamin E (VE) in bulk solution, solid films and single molecules. In solution and films, VE can not only significantly retard the photodegradation of P3HT but also enhance the fluorescence intensity. For individual P3HT molecules, with increasing VE concentrations, the on-time duration increases and the off-time duration becomes shorter. VE as natural antioxidants can not only donate electrons to the long-lived charged species but also quench the triplet states of CPs via energy transfer accelerating the depopulation process back to the ground state. The short duration time of the charged species and the triplet states provides higher fluorescence intensity. Furthermore, VE can also directly react with singlet oxygen or other reactive oxygen species (ROS) preventing them from reacting with CPs. These results not only provide an efficient strategy for improving the photostability of conjugated polymers in solution and films, but also shed light on better understanding the photophysics of conjugated polymers at single-molecule level.